Intrathyroidal Parathyroid Carcinoma: An Atypical Thyroid Lesion - Alharbi, Noran; Asa, Sylvia L.; Szybowska, Marta; Kim, Raymond H.; Ezzat, Shereen (Frontiers in Endocrinology, 2018)
Parathyroid carcinoma is a rare endocrine malignancy that is typically difficult to diagnose at presentation. Here, we report a 63 year-old man who had symptomatic hypercalcemia. Investigations revealed a thyroid nodule and a lateral neck mass that was biopsied and diagnosed as “suspicious for a neuroendocrine neoplasm.” He underwent total thyroidectomy with central and left neck node dissection. Histology and immunohistochemistry revealed an intrathyroidal angioinvasive parathyroid carcinoma with lymph node metastases. The tumor showed loss of parafibromin expression; germline testing revealed no pathogenic germline variants of CDC73, suggesting either a cryptic germline variant or a sporadic malignancy. Multiple pulmonary nodules consistent with metastatic disease explained persistent hypercalcemia and the patient was treated with denosumab as well as Sorafenib resulting in early regression of the lung nodules. This case illustrates an unusual parathyroid carcinoma with respect to anatomic presentation and the importance of complete pathological workup in securing the diagnosis. The management of these rare malignancies is discussed.